The impact of PROGRESA on community social relationships: final report - Adato, Michelle (International Food Policy Research Institute, 2000)
PROGRESA’s objective is to provide Mexican families living in extreme poverty access to opportunities for meeting their basic education, health and nutritional needs. It provides cash benefits linked to children’s school attendance and to families’ regular clinic visits, as well as health education and nutritional supplements. Economic analysis of PROGRESA’s system of household targeting found moderate advantages in relation to hypothetical geographic targeting or no-targeting scenarios. However, targeting involves social costs that need to be weighed into the analysis of the costs and benefits of alternative targeting systems. The research reported here examines these social costs, focusing on community social relationships, which can be seen as forms of social capital. Social capital is widely believed to be a factor in people’s ability to move out of poverty and facilitating development; thus, in addition to the intrinsic importance of strengthened or weakened social relationships, the extent to which PROGRESA contributes to or detracts from social capital has implications for the achievement of the program’s ultimate aims. Specifically, this report addresses the following questions: How do people in PROGRESA communities feel about the selection system? Is it perceived as fair, in concept and application? How do people feel as designated beneficiaries and non-beneficiaries? How does this differentiation affect the relationships between people in the two groups? Is there new social capital built as a result of PROGRESA?